How does caffeine affect the athlete`s body? - Shuvalova, N.; Lezhenina, S.; Akimova, V.; Grigorieva, M.; Zorin, S. (BIO Web of Conferences, 2020)
The purpose of the research is to carry out a theoretical analysis and generalization of modern scientific and methodological literature on the problem of the caffeine impact intake on the body of athletes. The results of experimental researches indicate a positive effect of caffeine intake on the indices of the anaerobic tests results and on the speed-strength indices. It has also been found that caffeine in combination with creatine enhances each other`s actions and has a positive effect on endurance performance. When evaluating the effect of caffeine on the athlete`s body, it was found that caffeine affects the production of lactic acid. It turned out that lactic acid is formed even at rest, as a side effect of taking caffeine. It is found that caffeine inhibits the activity of the enzyme phosphodiesterase. It was found that caffeine increases the secretion of endomorphins and, due to this, has an analgesic effect.